Acute kidney injury during fasting in Ramadhan in a patient with nephrolithiasis – a case report - Shalihin, Mohd Shaiful Ehsan; Mukhali, Hassan Basri (Asia Pacific Higher Learning Sdn Bhd., Lincoln University College, Malaysia, 2020)
Ramadhan fasting is a religious obligation for every Muslim since the era of Prophet Muhammad (peace upon him). Not only as a symbol of worship and obeying the command of the Creator, but it is also found to provide several health benefits. However, some patients might develop complications while observing Ramadan fasting, especially those with pre-existing medical condition or patient who is on certain medications. We would like to report a patient with gouty arthritis without a prior diagnosis of renal disease who was taking a urate-lowering agent and nonsteroidal anti-inflammatory drugs (NSAIDs) and presented to us with acute renal impairment during Ramadan fasting. Luckily, his renal function was improved with rehydration and cessation of NSAIDs. This case highlights the possible renal complication of Ramadan fasting among patient who takes regular NSAIDs and does not consume adequate fluid during sahur and breaking fast. Thus, identification and proper counselling of a patient with regular consumption of NSAIDs is vital before Ramadan begins.